Detection of Norovirus and Sapovirus from diarrheic dogs and cats in Japan - Soma, Takehisa; Nakagomi, Osamu; Nakagomi, Toyoko; Mochizuki, Masami (Microbiology and immunology, 2015)
Norovirus (NoV) and sapovirus (SaV) are important causes of human diarrhea. In this study, between 2007 and 2014 fecal samples were collected from 97 dogs and 83 cats with diarrhea and examined to determine the prevalence of NoV and SaV infections in Japan. To detect caliciviruses, approximately 300 bases targeting the polymerase gene were amplified using RT-PCR and subjected to phylogenetic and homology analyses. Specific PCR products were obtained from four canine and nine feline samples: two canine and one feline isolate were classified as NoV, two canine isolates as SaV and the remaining eight feline isolates as vesivirus (VeV). The three NoV isolates were classified into the same clade as that of known canine and feline NoVs; their homologies (75.9-92.3%) were higher than those with human genogroup IV (GIV) NoVs (59.1-65.9%). The homology of the feline NoV isolate with previously reported feline NoV isolates was particularly high (91.7-92.3%). Regarding SaV, the two canine isolates were classified into the same clade as known canine SaVs and their homologies (72.5-86.5%) were higher than those with other mammal SaVs (20.7-58.0%). The eight feline VeV isolates were assumed to be feline calicivirus. The present study is the first report of the presence of NoV- and SaV-infected dogs and cats in Japan. The findings suggest there are species-specific circulations of NoV and SaV among dogs and cats, in Japan.